Effect of Blastocystis sp. in dengue patients—Increase in the treatment cost and exacerbation of symptoms - Roques, Pierre; Thergarajan, Gaythri; Kumar, Suresh; Bhassu, Subha; Omar, Sharifah Faridah Syed; Rampal, Sanjay (Public Library of Science, 2019)
Increasing incidences of dengue have become a global health threat with major clinical manifestation including high fever and gastrointestinal symptoms. These symptoms were also expressed among Blastocystis sp. infected individuals, a parasite commonly seen in human stools. This parasite has been previously reported to replicate faster upon exposure to high temperature. The present study is a hospitalized-based cross-sectional study involved the collection of faecal sample from dengue patients. Stool examination was done by in vitro cultivation to isolate Blastocystis sp. Growth pattern of all the positive isolates were analyzed to identify the multiplication rate of Blastocystis sp. isolated from dengue patients. Distribution of Blastocystis sp. among dengue patients was 23.6%. Dengue patients who were positive for Blastocystis sp. infection denoted a significantly higher fever rate reaching 38.73C (p<0.05) compared to the non-Blastocystis sp. infected patients (38.44C). It was also found that Blastocystis sp. infected patients complained of frequenting the toilet more than five times a day (p<0.05) compared to those who were non-Blastocystis sp. infected. At the same time, the duration of hospitalization was significantly longer (p<0.05) for Blastocystis sp. infected dengue patients compared to the non-Blastocystis sp. infected patients. Besides, Blastocystis sp. isolated from dengue patients (in vivo thermal stress) showed a higher growth rate compared to the non-dengue isolated which was exposed to high temperature (in vitro thermal stress). Our findings suggest that presence of Blastocystis sp. during dengue infection could trigger the increase of temperature which could be due to highly elevated pro inflammatory cytokines by both parasitic and virus infection. This could justify why the temperature in Blastocystis sp. infected dengue patients is higher compared to the non-Blastocystis sp. infected patients. Higher temperature could have triggered a greater parasite multiplication rate that contributed to the aggravation of the gastrointestinal symptoms. © 2019 Thergarajan et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.